STRATEGI DIGITAL MARKETING DENGAN INSTAGRAM DAN TIKTOK PADA BUTIK DOT.ID - Hidayatullah, M.F.; Rafidah, Nathania Nur; Masruroh, Nikmatul; Mauliyah, Nur Ika (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2023)
The use of digital marketing is a marketing demand. There is no choice for companies that want to survive not to take advantage of digital marketing. This research describes a digital marketing strategy, using the Instagram and TikTok applications. Instagram and TikTok are photo and video-based digital applications, which are currently widely used by businesses in marketing their products. This field research used a qualitative approach with descriptive analysis. The validity of the data was tested with a triangulation technique. The results showed: First, the Dot.id Boutique digital marketing strategy with photo and video-based promotions through Instagram and TikTok media features such as Instagram stories, Instagram reels, live Instagram, TikTokshop, TikTok video content and also supported by endorsements, sales and giveaways; Second, the impact that Dot.id boutiques get through digital marketing, namely digital marketing is more effective and efficient than conventional marketing, get feedback or feedback from consumers, and get increased revenue.